Montagem de um conjunto experimental destinado á verificação do princípio da incerteza de Heisenberg - Abrego, José Ramon Beltran [UNESP]; Yamaguchi, Dan Alec [UNESP]; Liboni, Tarcisio Alves [UNESP]; Barbosa, Antonio Aparecido [UNESP]; Belusi, Marcelino [UNESP]; Salinas, Paulo Roberto [UNESP]; Bossa, Guilherme Volpe [UNESP] (My University, 2013)
In this paper we present the an experimental setup to check the Heisenberg uncertainty principle. The description of the experimental setup and of the theoretical foundations is aimed at promoting the familiarization of the students with the involved concepts. © The Sociedade Brasileira de Física.
Assembly of an experimental system for the verification of heisenberg's uncertain principle
Keywords: Heisenberg's uncertainty principle; Uncertainty principle